2021
DOI: 10.1093/trstmh/trab109
|View full text |Cite
|
Sign up to set email alerts
|

The seroprevalence of severe acute respiratory syndrome coronavirus 2 in Delhi, India: a repeated population-based seroepidemiological study

Abstract: Background Three rounds of a repeated cross-sectional serosurvey to estimate the change in seroprevalence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) were conducted from August to October 2020 in the state of Delhi, India, in the general population ≥5 y of age. Methods The selection of participants was through a multistage sampling design from all 11 districts and 280 wards of the city-state, with multista… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 23 publications
5
14
1
Order By: Relevance
“…In this study, nearly one in four participants with a history of COVID-19 disease were seronegative, a finding consistent with previous serosurveys where antibodies to COVID-19 were lacking in a substantial proportion of the participants [8]. These findings could be attributed to the growing evidence, suggestive of the waning of IgG antibodies, especially during asymptomatic and mild illness, although the risk of COVID-19 reinfection in previously infected patients remains low [16,17].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In this study, nearly one in four participants with a history of COVID-19 disease were seronegative, a finding consistent with previous serosurveys where antibodies to COVID-19 were lacking in a substantial proportion of the participants [8]. These findings could be attributed to the growing evidence, suggestive of the waning of IgG antibodies, especially during asymptomatic and mild illness, although the risk of COVID-19 reinfection in previously infected patients remains low [16,17].…”
Section: Discussionsupporting
confidence: 88%
“…In this serosurvey, a majority of the participants had detectable antibodies to SARS-CoV-2 from past infections with nearly uniform district-level trends. In comparison to the three months preceding the survey [8], the antibody seroprevalence in January showed a more than two times increase, coinciding with a rapid decline in the test-positivity rate and the daily new incident cases, suggestive of a high population-level immunity. However, the high seroprevalence through natural infection was insufficient to achieve herd immunity and avert the next wave of the pandemic in Delhi since November 2020, with nearly 0.737 million cases including 11,075 deaths recorded from April to May 2021 [12].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Serial serosurveys previously indicated that the age and sex weighted seroprevalence in Delhi in the ≥5 population increased from 24.71% (95% CI 24.01 to 25.42) in August-October 2020 to 50.52% (95% CI 49.94 to 51.10 in January 2021 [6, 7].…”
Section: Introductionmentioning
confidence: 99%